ETIKA SUFISTIK DALAM PENANGANAN RUQYAH SYAR’IYAH SUFISTIC ETHICS IN HANDLING RUQYAH SYAR’IYAH - Badrudin, Badrudin; Mita, Sela; Rizki Azkiya, Muhammad (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2023)
This article is entitled "Sufistic ethics in handling ruqyah syar'iyah". This research aims to find out how to handle ruqyah and how to treat it. This research uses a qualitative approach. To obtain more accurate data, researchers used several literature or library materials (Library Research), namely by searching for data through reading reference books and available publication materials and then putting them together to form one relevant unit. Ruqyah syar’iyah can also be an effective therapy for patients who experience physical and psychological illnesses (stress or madness). Islam takes seriously the rules of treatment and who carries out treatment on patients so that it is in line with the demands of society and this is what differentiates Islamic treatment from improper treatment. It is mandatory for a convert to have aqidah that is clean from prohibited things, always carry out orders and abandon the prohibitions of Allah SWT, in order to obtain true healing and be blessed by Allah SWT. The ruqyah treatment process begins with the healer reading ruqyah verses to the patient. When reciting verses from the Koran, the patient will react as if his whole body is shaking, vomiting something, becoming unconscious. Patients cannot expect or depend completely on the teacher. But the patient must be persistent in carrying out the practices that have been taught by the convert to protect himself. By carrying out these practices with istiqomah, he will give strength to the patient's spiritual and physical health. Furthermore, patients can get healing and avoid being exposed to non-medical diseases (jinn and demons) again